Penggunaan Media Audio Visual Untuk Meningkatkan Minat Belajar Matematika Kelas V SDN 06 Batu Taba - Hamanda, Gustia (Universitas Sebelas Maret, 2020)
The purpose of this study was to increase the interest in learning mathematics for fifth grade students at SDN 06 Batu Taba, Ampek Angkek District, Agam Regency, West Sumatra. The research method used is the classroom action research method (CAR) which was carried out at SDN 06 Batu Taba in the 2018/2019 school year for 20 Class V students. The research design used is classroom action research. This research was carried out for two actions (cycles). Each action includes planning, implementation, observation and reflection. The technique of collecting data is through a learning interest test. The results showed that there was an increase in interest in learning through the use of audio-visual media for class V SDN 06 Batu Taba. The increase in this study was quite significant, namely from the average interest in learning in the first cycle of 71.25%, it rose to 80.42% in the second cycle or increased by 9.17%. An increase also occurred in classical learning completeness, from 60% in the first cycle to 85% in the second cycle or an increase of 25%. This means that the results obtained have met the criteria for classical student learning completeness as determined in the indicators of this study, which is 80% and individual learning completeness is 65.